Comparative Analysis of inv Gene Structure in Strains of Plague and Pseudotuberculosis Agents - G.N. Odinokov; G.A. Eroshenko; V.V. Kutyrev (Проблемы особо опасных инфекций, 2009)
Gene inv encoding one of the important pathogenicity factors of pseudotuberculosis agent was analyzed as regards its structure and function in plague microbe of the main and non-main subspecies and pseudotuberculosis microbe. The structure of gene inv was shown to be affected by introduction of insertion sequence IS1541 in all studied Yersinia pestis strains of non-main and main subspecies. This evidences that the loss of functional activity of this gene took place at initial stage of plague agent evolution.